Predators control pests and increase yield across crop types and climates: a meta-analysis - Boldorini, Gabriel X; Mccary, Matthew A; Romero, Gustavo Q; Mills, Kirby L; Sanders, Nathan J; Reich, Peter B; Michalko, Radek; Gonçalves-Souza, Thiago (Proceedings. Biological sciences, 2024)
Pesticides have well-documented negative consequences to control crop pests, and natural predators are alternatives and can provide an ecosystem service as biological control agents. However, there remains considerable uncertainty regarding whether such biological control can be a widely applicable solution, especially given ongoing climatic variation and climate change. Here, we performed a meta-analysis focused on field studies with natural predators to explore broadly whether and how predators might control pests and in turn increase yield. We also contrasted across studies pest suppression by a single and multiple predators and how climate influence biological control. Predators reduced pest populations by 73% on average, and increased crop yield by 25% on average. Surprisingly, the impact of predators did not depend on whether there were many or a single predator species. Precipitation seasonality was a key climatic influence on biological control: as seasonality increased, the impact of predators on pest populations increased. Taken together, the positive contribution of predators in controlling pests and increasing yield, and the consistency of such responses in the face of precipitation variability, suggest that biocontrol has the potential to be an important part of pest management and increasing food supplies as the planet precipitation patterns become increasingly variable.
Keywords: klimatické změny; Pesticides; biological control; resident agents; pest control; pesticidy; Climate Change; biocontrol; Uncertainty; natural enemies; ekosystém; natural predators; nejistota; Ecosystem